2011
DOI: 10.1152/ajpregu.00528.2010
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and functional differences between brain and spinal cord mitochondria underlie different predisposition to pathology

Abstract: Mitochondrial dysfunctions contribute to neurodegeneration, the locations of which vary among neurodegenerative diseases. To begin to understand what mechanisms may underlie higher vulnerability of the spinal cord motor neurons in amyotrophic lateral sclerosis, compared with brain mitochondria, we studied three major functions of rat brain mitochondria (BM) and spinal cord mitochondria (SCM) mitochondria: oxidative phosphorylation, Ca 2ϩ sequestration, and production of reactive oxygen species (ROS), using a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 53 publications
(71 reference statements)
1
54
0
1
Order By: Relevance
“…Nevertheless, our comparative studies of metabolic properties of BM and SCM suggest that potentially the loss of morbidity could be explained by different patterns of substrates metabolism and associated ROS generation in BM and SCM studied in 2007 and 2010. In 2008 we found that BM and SCM isolated from the wild type Sprague Dawley rats began to show metabolic features that were different from those described earlier for the same strain of the wild type and tgSOD1 rats (Panov et al, 2009(Panov et al, , 2011a. In this work we present a comparison of metabolic phenotypes and the substrate-dependent ROS generation in the wild type and transgenic rats with mutant G93A Cu/Zn-superoxide dismutase gene isolated in 2007 and 2010.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…Nevertheless, our comparative studies of metabolic properties of BM and SCM suggest that potentially the loss of morbidity could be explained by different patterns of substrates metabolism and associated ROS generation in BM and SCM studied in 2007 and 2010. In 2008 we found that BM and SCM isolated from the wild type Sprague Dawley rats began to show metabolic features that were different from those described earlier for the same strain of the wild type and tgSOD1 rats (Panov et al, 2009(Panov et al, , 2011a. In this work we present a comparison of metabolic phenotypes and the substrate-dependent ROS generation in the wild type and transgenic rats with mutant G93A Cu/Zn-superoxide dismutase gene isolated in 2007 and 2010.…”
Section: Introductionmentioning
confidence: 68%
“…The familial cases with mutations in the SOD1 gene have basically the same mechanism of motor neuron death, but, because mutated SOD1 protein is exceptionally sensitive to oxidative damage, the loss of Cu and Zn may occur at relatively low levels of H 2 O 2 formation by neuronal mitochondria. The predominant involvement of spinal cord can be accounted for by metabolic and structural features of spinal cord and SCM, which were published elsewhere (Panov et al, 2011a(Panov et al, , 2011b.…”
Section: Wwwintechopencommentioning
confidence: 99%
See 2 more Smart Citations
“…Mitochondria isolated from the neural tissue (brain, spinal cord) have distinct metabolic properties regarding the extent of ROS produced upon oxidation of respiratory substrates (Panov et al, 2011). Especially in G93A-SOD1 transgenic rats, brain and spinal cord mitochondria generate 5-7 fold more ROS than mitochondria of corresponding wild-type tissues.…”
Section: Toxic Mechanism Referencesmentioning
confidence: 99%